2008
DOI: 10.1007/s00018-008-8016-3
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase in intestinal cell differentiation involves G2/M cell cycle arrest

Abstract: Here we examine differentiation of the intestinal cell line Caco-2 following exposure to sodium butyrate (NaBT), using alkaline phosphatase (ALP) activity and carcinoembryonic antigen (CEA) levels as markers of differentiation. We show that acetylcholinesterase (AChE) activity and RNA levels increase during differentiation. Treatment with AChE inhibitors or knockdown of AChE levels by shRNA markedly decrease ALP and CEA levels in a concentration- and time-dependent manner. Finally, our observations suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 26 publications
1
17
0
1
Order By: Relevance
“…Previous studies have determined that apoptosis can also be induced in Caco-2 cells due to modification of phases of the cell cycle by redox modulation, specifically G1 to the S phase [41]. In a study by Xiang et al [42], butyrate increased the number of cells in the M phase and decreased cells in the S phase [42]. This inconsistency with the current study was possibly due to a lower dose of butyrate (1 m M ) and a shorter assay period [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have determined that apoptosis can also be induced in Caco-2 cells due to modification of phases of the cell cycle by redox modulation, specifically G1 to the S phase [41]. In a study by Xiang et al [42], butyrate increased the number of cells in the M phase and decreased cells in the S phase [42]. This inconsistency with the current study was possibly due to a lower dose of butyrate (1 m M ) and a shorter assay period [42].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Xiang et al [42], butyrate increased the number of cells in the M phase and decreased cells in the S phase [42]. This inconsistency with the current study was possibly due to a lower dose of butyrate (1 m M ) and a shorter assay period [42]. However, Matthews et al [1] demonstrated that butyrate (5 m M ) treatment of Caco-2 cells reduced cells in G0/G1 and arrested cells in the S and G2/M phases [1].…”
Section: Discussionmentioning
confidence: 99%
“…This esterase activity is the target of widely used pesticides and pharmaceuticals (Mileson et al, 1998;Pope et al, 2005), yet the broad expression of AChE outside of the nervous system (Anderson et al, 2008;Bertrand et al, 2001;Bicker et al, 2004;Drews, 1975) and similarity to adhesion molecules (Botti et al, 1998;Darboux et al, 1996) suggest that it has additional functions. Indeed, in neuronal and non-neuronal cell lines, AChE promotes cell-substrate adhesion (Inkson et al, 2004;Johnson and Moore, 1999;Sharma et al, 2001;Syed et al, 2008), polarized cell migration (Anderson et al, 2008), cytoskeletal organization (Dupree and Bigbee, 1994;Keller et al, 2001) and cell differentiation (Grisaru et al, 1999;Xiang et al, 2008), independently of its esterase activity (Layer et al, 1993). However, the in vivo relevance of this putative multi-functionality is poorly substantiated, especially in non-neuronal contexts (Vogel-Hopker et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This esterase activity is the target of widely used pesticides and pharmaceuticals (Mileson et al, 1998;Pope et al, 2005), yet the broad expression of AChE outside of the nervous system (Anderson et al, 2008;Bertrand et al, 2001;Bicker et al, 2004;Drews, 1975) and similarity to adhesion molecules (Botti et al, 1998;Darboux et al, 1996) suggest that it has additional functions. Indeed, in neuronal and non-neuronal cell lines, AChE promotes cell-substrate adhesion (Inkson et al, 2004;Johnson and Moore, 1999;Sharma et al, 2001;Syed et al, 2008), polarized cell migration (Anderson et al, 2008), cytoskeletal organization (Dupree and Bigbee, 1994;Keller et al, 2001) and cell differentiation (Grisaru et al, 1999;Xiang et al, 2008), independently of its esterase activity (Layer et al, 1993). However, the in vivo relevance of this putative multi-functionality is poorly substantiated, especially in non-neuronal contexts (Vogel-Hopker et al, 2012).…”
Section: Introductionmentioning
confidence: 99%